2012
DOI: 10.1186/1741-7015-10-170
|View full text |Cite
|
Sign up to set email alerts
|

Substantial and reversible brain gray matter reduction but no acute brain lesions in ultramarathon runners: experience from the TransEurope-FootRace Project

Abstract: BackgroundDuring the extremely challenging 4,487 km ultramarathon TransEurope-FootRace 2009, runners showed considerable reduction of body weight. The effects of this endurance run on brain volume changes but also possible formation of brain edema or new lesions were explored by repeated magnetic resonance imaging (MRI) studies.MethodsA total of 15 runners signed an informed consent to participate in this study of planned brain scans before, twice during, and about 8 months after the race. Because of dropouts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Freund et al 15 demonstrated a reversible volume reduction of cerebral gray matter (6%) after 2 months of daily running during an ultramarathon, which is in line with the reversible cortical thinning (0.19%) on dehydration reported in our study. On the other hand, a recent study with low sample size 14 failed to reveal thinning of the cerebral cortex and shrinking of the hypothalamus/ thalamus, which are reversed on rehydration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Freund et al 15 demonstrated a reversible volume reduction of cerebral gray matter (6%) after 2 months of daily running during an ultramarathon, which is in line with the reversible cortical thinning (0.19%) on dehydration reported in our study. On the other hand, a recent study with low sample size 14 failed to reveal thinning of the cerebral cortex and shrinking of the hypothalamus/ thalamus, which are reversed on rehydration.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Streitbürger et al 14 demonstrated an increase in brain volume on ingestion of 3–4 L of water; however, they failed to show an effect of dehydration on brain volume by 2 days of restricted water intake. In a study on ultramarathon runners, Freund et al 15 described a reversible 6% cortical volume reduction with 2 months of daily running. Currently, there are no in vivo data on tissue water changes and associated morphometric changes involved in the osmoadaptation of normal brains.…”
mentioning
confidence: 99%
“…Only some studies corrected for age or overall brain volumes, some studies distinguished restricting from binge eating/purging anorexia nervosa while others did not, and the effects of comorbid diagnoses or medication were often not taken into account [12••]. Furthermore, the effects of acute dehydration and starvation [20] as well as excessive exercise [21] most likely have significant confounding effects that may not be directly related to the underlying ED-specific pathophysiology. Importantly, the global effects of malnutrition may obscure particularly in studies that showed widespread alterations across large cortical regions brain pathology that drives ED behavior.…”
Section: Research On Brain Volumementioning
confidence: 99%
“…Repeated and strenuous running exercises constitute a remarkable physical stressor requiring important mental effort. An example of this is the 64 day ultramarathon covering about 4,500 km from Bari, Italy to the North Cape, Norway used in the study of Freund et al [3], published in BMC Medicine . We expect the ultramarathon model to involve concurrent physical and mental demands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can probably be considered as one of the main challenges that would allow us to explore the finite resources of the human brain under natural field settings. Freund et al [3] have successfully explored some biometrical data and the cerebral structural changes occurring in 10 runners in response to chronic endurance running exposure, with the help of three identical magnetic resonance (MR) scanners (one was a mobile MR unit mounted on a truck trailer across Europe). The results of this unique study, which revealed no brain lesions, suggest that ultra-endurance runners likely have important mental effort prerequisites and an adapted training workload to cope with demands of ultramarathon running.…”
Section: Introductionmentioning
confidence: 99%